Contribution of Ethiopian green legacy on fruit crop production: a review - Massrie, Kelemu Dessie (Frontiers in Sustainable Food Systems, 2024)
The Ethiopian Green Legacy Initiative, launched in 2019, represents a pioneering effort in reforestation aimed at combating deforestation, restoring degraded landscapes, and enhancing environmental resilience. By the end of 2022, over 25 billion trees had been planted, with a target of 50 billion by 2030. This review explores the initiative's impact on fruit crop production, focusing on improvements in soil fertility, water resources, and pollinator conservation. The review systematically collects and evaluates information from various sources to assess the initiative's contributions to these areas. The initiative has significantly improved soil health, enhanced groundwater recharge, and created crucial habitats for pollinators, which have contributed to increased fruit crop yields and expanded production areas, particularly in regions like Oromia, SNNPR, and Amhara. Notable crops benefiting from these improvements include mangoes, avocados, citrus fruits, and bananas. However, the initiative faces challenges, including varying tree survival rates, climate-related impacts, and difficulties in policy integration. To ensure its long-term success, scaling up efforts, aligning the initiative with broader agricultural policies like the climate resilient green economy strategy, and investing in research on climate-resilient practices are essential to maximize the green legacy initiative's potential to enhance Ethiopia's food security, boost rural income, and support environmental sustainability.